Distance to the Neurovascular Bundle for Iliotibial Band Graft Passage During Anterior Cruciate Ligament Reconstruction: A Pediatric Cadaveric Study. Issue 8 (12th August 2022) - Thomas, Nicholas D.; Ayala, Salvador; Rohde, Matthew; Gupta, Anshal; Sanchez, Mark; Ellis, Henry; Tompkins, Marc; Wilson, Phil; Sherman, Seth; Green, Daniel; Ganley, Theodore J.; VandenBerg, Curtis; et al.
Background: The Micheli technique for anterior cruciate ligament (ACL) reconstruction (ACLR) has proven to be a reliable method with a minimal risk for growth disturbance among skeletally immature patients. Purposes: To evaluate the Micheli technique of iliotibial band (ITB) graft passage for ACLR using cadaveric knee models and to measure the distance between the surgical instrument tip and the neurovascular bundle in the posterior knee joint: specifically, the peroneal nerve, tibial nerve, and popliteal artery. Study Design: Descriptive laboratory study. Methods: Gross dissection was performed on 17 pediatric cadaveric knees (12 male and 5 female) aged between 4 and 12 years. To simulate ITB graft passage, we passed a curved-tip hemostat clamp through the posterior capsule, with the knee flexed from 90° to 100°. Next, clinical photographs were taken, and digital imaging software was used to measure the distance in centimeters from the clamp tip to each respective neurovascular structure. Results: The mean distances from the clamp tip to the tibial nerve, popliteal artery, and peroneal nerve were 0.875 cm (range, 0.468-1.737 cm), 0.968 cm (range, 0.312-1.819 cm), and 1.149 cm (range, 0.202-2.409 cm), respectively. Mean values were further calculated for age groups of ≤8, 9-10, and 11-12 years. The mean distance from the clamp tip to the peroneal nerve was 1.400 cm larger for 11- to 12-year-old specimens than for ≤8-year-old specimens (95% CI, 0.6-2.2 cm; P = .005). Conclusion: The neurovascular structures in the posterior knee were in close proximity to the path of graft passage, with distances <1 cm in many specimens in this study. When passing the graft through the knee for an over-the-top position, surgeons should consider these small distances between the path of graft passage and critical neurovascular structures. Clinical Relevance: As the incidence of ACL tears is continuously increasing within the pediatric population, there are a larger number of ACLR procedures being performed. Although neurovascular injuries during ACLR are rare, this study clarifies the close proximity of neurovascular structures during ITB graft passage using the Micheli technique of ACLR.